Assistance In School Asset Administration Through The Preparation Of Room Inventory Cards (KIR) At SD Negeri Inpres Yoka Pantai In Jayapura City - Maylen K. P. Kambuaya; Pascalina V.S Sesa; Whydia A. Issan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
In practice, the management of fixed assets in public schools is still limited to recording by the Education Office. Schools are not required to manage assets independently, but are only tasked with reporting additional assets obtained through the Special Allocation Fund (DAK) for Physical Education and BOS Funds. However, the recording of assets sourced from Central Government Assistance Expenditure has not been fully carried out, although the amount is quite large every year. This has the potential to pose a risk of data overlap, corruption, or loss of assets. In addition, asset registration by the Education Office using an asset recording application has not been accompanied by an adequate verification process, only based on the results of reconciliation between the school and the Accounting Division of the Financial Agency. To improve the governance of fixed assets in schools, this community service program (PKM) aims to assist SD Negeri Inpres Yoka Pantai, Heram District, Jayapura City in conducting asset inventory by compiling a Room Inventory Card (KIR). Activities include providing understanding of asset management and assistance in the asset inventory process in each school room. The conclusion that can be made from the School Asset Administration Assistance activity through the Preparation of KIR at SD Negeri Inpres Yoka Pantai Heram District, Jayapura City is to increase the knowledge and understanding of school asset managers, in this case the principal who is assisted by teachers in managing school assets, which increasing the school's awareness of the importance of asset management and the formation of an orderly administrative culture.